The elephants of Gangala-na-Bodio - Robert Malpas (Pachyderm)
Notes the historical background and present status of the elephant domestication project at Gangala-na-Bodio near Garamba National Park. Four elephant females presently kept on the station are used on a daily basis to collect fodder. The potential to utilize trained elephants for use in tourism is mentioned